2018
DOI: 10.1155/2018/7987589
|View full text |Cite
|
Sign up to set email alerts
|

Use of Silica Fume and GGBS to Improve Frost Resistance of ECC with High‐Volume Fly Ash

Abstract: Fly ash (FA) has been an important ingredient for engineered cementitious composite (ECC) with excellent tensile strain capacity and multiple cracking. Unfortunately, the frost resistance of ECC with high-volume FA has always been a problem. is paper discusses the influence of silica fume (SF) and ground-granulated blast-furnace slag (GGBS) on the frost resistance of ECC with high volume of FA. Four ECC mixtures, ECC (50% FA), ECC (70% FA), ECC (30% FA + 40% SL), and ECC (65% FA + 5% SF), are evaluated by free… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…Therefore, the PVA fibers employed in the design mix compositions of this current study are more effective compared to PP fibers in terms of flexural performance. The findings in this study confirm that PVA fibers are better than PP fibers to be used in developing ECC that exhibit strain hardening and multiple fine cracking behaviors, and this is parallel with the evidence found in previous investigations (Huang & Zhang, 2014;Li et al, 2001;Li et al, 2004;Liu et al, 2018;Pakravan et al, 2018;Yang & Li, 2014;Yang et al, 2007).…”
Section: Comparison Of Flexural Behavior With Previous Studysupporting
confidence: 90%
“…Therefore, the PVA fibers employed in the design mix compositions of this current study are more effective compared to PP fibers in terms of flexural performance. The findings in this study confirm that PVA fibers are better than PP fibers to be used in developing ECC that exhibit strain hardening and multiple fine cracking behaviors, and this is parallel with the evidence found in previous investigations (Huang & Zhang, 2014;Li et al, 2001;Li et al, 2004;Liu et al, 2018;Pakravan et al, 2018;Yang & Li, 2014;Yang et al, 2007).…”
Section: Comparison Of Flexural Behavior With Previous Studysupporting
confidence: 90%
“…They found that ordinary Portland cement concrete reached a mass loss rate of 5% after 45 freeze-thaw cycles, while alkali-activated concrete required 98 freeze-thaw cycles to reach the same mass loss rate. Liu et al [130] studied the effect of silica fume on the freeze-thaw resistance of alkali-activated fly ash/slag cementitious materials through experiments. The results showed that the addition of silica fume led to more damage and deterioration of the hardened samples under freeze-thaw cycles.…”
Section: Freeze-thaw Resistancementioning
confidence: 99%
“…Despite their remarkable properties, ECCs face challenges associated with their high reliance on ordinary Portland cement (OPC), leading to significant environmental and economic concerns [2]. To tackle these challenges, researchers have been exploring the use of various waste materials, such as silica fume, slag, and class C or F fly ash as partial replacements for OPC in ECCmix designs [3,4]. In addition, studies are now exploring alternative design strategies that aim to minimize or completely eliminate the need for OPC, considering its substantial contribution (6-10%) to global anthropogenic CO 2 emissions [5,6].…”
Section: Introductionmentioning
confidence: 99%